2022
DOI: 10.31729/jnma.7615
|View full text |Cite
|
Sign up to set email alerts
|

Non-strabismic Binocular Vision Dysfunction among the Medical Students of a Teaching Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Non-strabismic binocular vision dysfunctions are visual disorders that affect the person’s binocular vision and visual outcome while performing near tasks and are very common among medical students. This study aimed to find out the prevalence of non-strabismic binocular vision dysfunction among the medical students of a teaching hospital. Methods: A descriptive cross-sectional study was conducted among medical students of a teaching hospital from 25 April 2022 to 25 May 2022. Ethical approval was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…García-Muñoz [2] Shrestha [3] Franco [4] Darko-Takyi [5] Liu [6] Current showed the prevalence rate of the 18-35-year-old population to be 32.05% [4] and 36.1% [6] , respectively. Meanwhile, the prevalence rate of college students from Spain, Malaysia, Ghana, and Nepal was 13.15% [2] , 40% [12] , 34.3% [5] , and 27.82% [3] , respectively.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…García-Muñoz [2] Shrestha [3] Franco [4] Darko-Takyi [5] Liu [6] Current showed the prevalence rate of the 18-35-year-old population to be 32.05% [4] and 36.1% [6] , respectively. Meanwhile, the prevalence rate of college students from Spain, Malaysia, Ghana, and Nepal was 13.15% [2] , 40% [12] , 34.3% [5] , and 27.82% [3] , respectively.…”
Section: Studymentioning
confidence: 99%
“…García-Muñoz [2] Shrestha [3] Franco [4] Darko-Takyi [5] Liu [6] Current showed the prevalence rate of the 18-35-year-old population to be 32.05% [4] and 36.1% [6] , respectively. Meanwhile, the prevalence rate of college students from Spain, Malaysia, Ghana, and Nepal was 13.15% [2] , 40% [12] , 34.3% [5] , and 27.82% [3] , respectively. The findings of this study revealed a higher frequency rate of 36.71% among optometric outpatients of Guangxi Medical University, which is similar to the report of Liu et al [6] .…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Refractive disorders, retinal and neurological diseases and ageing can be accompanied by stereovision loss [6][7][8][9]. Non-strabismic accommodative and vergence dysfunctions are common vision anomalies encountered frequently and are usually associated with extensive near work [10,11]. The individual level of binocular cooperation in non-strabismus people depends on many factors, including visual acuity, contrast sensitivity, accommodation, vergence, proprioception, brain activity and so on [3,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of fusional vergence is fundamental in standard optometric exams, as it provides information about the patient’s binocular vision status and, together with the results of other optometric tests, is useful to diagnose binocular vision dysfunctions [ 6 , 7 ]. The prevalence of non-strabismic binocular vision dysfunctions has been well documented in the literature, although results differ between studies reporting prevalence ranges from 13.5% to 32%; [ 8 11 ] 2.29% to 15.81% of these associated with accommodation disorders [ 8 , 10 , 11 ], and 8% to 12.9% related to vergence disorders [ 8 , 12 ]. Convergence insufficiency (CI) and accommodative insufficiency (AI) are the most common non-strabismic binocular dysfunctions with a prevalence ranging from 3.43% to 10.3% for CI [ 8 , 9 , 11 , 13 ] and 11.5% to 5.3% for AI [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%